DINÁMICA DEL PAISAJE AGRARIO DE SAN PATRICIO DEL CHAÑAR (NEUQUÉN, ARGENTINA) A TRAVÉS DE IMÁGENES SATELITALES - Florencia G. Finessi; Damián Groch (Boletín Geográfico)
This study’s aim is to describe the agricultural landscape dynamics in San Patricio del Chañar (Province of Neuquén, Argentina). The characteristics of the area in which the agrarian landscape is located are discussed dealing with some theoretical elements and methodologies. The historical organization process that shaped the present urban patterns taking into account the social actors involved using satellite imagery analysis. Satellite information is used to analyse how agricultural elements of this landscape have changed in the past decade. This allowed to recognize natural zones, its influences in social land use development and the organization process that has taken place during the final decades of the 20th century and the first decade of the 21th century.